Mfsd2a is important for maintaining epidermal homeostasis - Bernice H. Wong; Kunal Mishra; Cheen Fei Chin; Dwight L. A. Galam; Bryan C. Tan; Mei Ding; Federico Torta; Jacques Behmoaras; Alvin W. C. Chua; David L. Silver (Proceedings of the National Academy of Sciences, 2026)
The skin epidermis is a multilayered lipid rich organ completely reliant on exogenous delivery and uptake of the essential fatty linoleate for the synthesis of acylceramides required for barrier function. Disruption of the epidermal skin barrier is a common clinical feature for prevalent diseases such as atopic dermatitis and psoriasis. The granulosum layer of the epidermis contains specialized secretory keratinocytes that synthesize and secrete lamellar bodies (LB), making it likely that this epidermal layer has a high demand for phosphatidylcholine. While the pathway for acylceramide biosynthesis and roles in barrier formation has been largely elucidated, the mechanisms by which keratinocytes acquire phospholipid for the demands of lipid barrier maintenance and repair are not entirely understood. Here, we demonstrate that Mfsd2a, a lysophosphatidylcholine (LPC) transporter, is predominantly expressed in keratinocytes and mediates the uptake of a plasma-derived LPC fluorescent probe. Epidermal-specific deficiency of Mfsd2a in mice resulted in dermatitis and defective desquamation of the epidermis, and inducible deletion of Mfsd2a in primary mouse keratinocytes in vitro prevented their epidermal stratification. Untargeted lipidomic analysis indicated that Mfsd2a deficiency resulted in a significantly altered phospholipidome, with specific reductions in linoleic acid in phosphatidylcholine and triglycerides in the epidermis. Functional studies using primary human keratinocytes demonstrated that LPC-oleate and LPC-linoleate promoted keratinocyte differentiation in a Mfsd2a-dependent manner. Our findings identify a pathway by which keratinocytes acquire plasma-derived LPC via Mfsd2a transport for the maintenance of normal keratinocyte phosphatidylcholine pools and for optimal keratinocyte differentiation.